Kinetics of hydroformylation of 1-octene in ionic liquid-organic biphasic media using rhodium sulfoxantphos catalyst - Deshpande, R. M.; Kelkar, Ashutosh A.; Sharma, A.; Julcour-Lebigue, C.; Delmas, Henri (Chemical Engineering Science, 2011)
Biphasic hydroformylation of 1-octene was performed using rhodium sulfoxantphos catalyst dissolved in [BuPy][BF(4)] ionic liquid. Preliminary experiments proved this system to retain the catalytic complex within the ionic liquid phase and to maintain a high selectivity towards the linear aldehyde (n:iso ratio of 30) over several cycles. Process parameter investigation showed a first order dependence of the initial rate with respect to the catalyst and 1-octene concentrations, but a more complex behavior with respect to hydrogen (fractional order) and carbon monoxide partial pressures (inhibition at high pressures). Different mathematical models were selected based on the trends observed and evaluated for data fitting. Also, rate models were derived from a proposed mechanism, using Christiansen matrix approach. To calculate concentrations of substrates in the catalytic phase as required by this kinetic modeling, solubility measurements were preformed for the gases (pressure drop technique), as well as for 1-octene and n-nonanal (thermogravimetry analysis). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biphasic catalysis; Butylpyridinium tetrafluoroborate; kinetics; Parameter identification; Reaction engineering; solubility

Assessing therapeutic potential of molecules: molecular property diagnostic suite for tuberculosis - Gaur, A. S.; Bhardwaj, A.; Sharma, A.; John, L.; Vivek, M. R.; Tripathi, N.; Bharatam, P. V.; Kumar, R.; Janardhan, S.; Mori, A.; Banerji, A.; Lynn, A. M.; et al. (Journal of Chemical Sciences, 2017)
Abstract: Molecular Property Diagnostic Suite (MPDS TB) is a web tool (http://mpds.osdd.net) designed to assist the in silico drug discovery attempts towards Mycobacterium tuberculosis (Mtb). MPDS TB tool has nine modules which are classified into data library (1–3), data processing (4–5) and data analysis (6–9). Module 1 is a repository of literature and related information available on the Mtb. Module 2 deals with the protein target analysis of the chosen disease area. Module 3 is the compound library consisting of 110.31 million unique molecules generated from public domain databases and custom designed search tools. Module 4 contains tools for chemical file format conversions and 2D to 3D coordinate conversions. Module 5 helps in calculating the molecular descriptors. Module 6 specifically handles QSAR model development tools using descriptors generated in the Module 5. Module 7 integrates the AutoDock Vina algorithm for docking, while module 8 provides screening filters. Module 9 provides the necessary visualization tools for both small and large molecules. The workflow-based open source web portal, MPDS TB 1.0.1 can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. Graphical Abstract: SYNOPSIS: A web-based MPDS TB Galaxy tool is developed for assessing therapeutic potential of molecules. MPDS TB is categorized into Data Library, Data Processing and Data Analysis. It can be a potential enabler for scientists engaged in drug discovery in general and in anti-TB research in particular. [Figure not available: see fulltext.] © 2017, Indian Academy of Sciences.
Keywords: chemical analysis; Chemoinformatics; computational chemistry; Diagnosis; Drug discovery portal; Information analysis; Libraries; Molecular graphics; Molecules; Neglected diseases; Open science; Portals; tuberculosis; Web-based technology; Websites

Enhancement of field electron emission in topological insulator Bi2Se3 by Ni doping - Mazumder, K.; Sharma, A.; Kumar, Y.; Bankar, P.; More, M. A.; Devan, R.; Shirage, P. M. (Physical Chemistry Chemical Physics, 2018)
Nanostructures of bismuth selenide (Bi2Se3), a 3D topological insulator material, and nickel (Ni) doped Bi2Se3 samples were prepared by a hydrothermal method to explore the field emission properties. An enrichment in the field electron emission (FE) properties in terms of the threshold and turn-on field values of Bi2Se3 and Ni doped Bi2Se3 nanostructures was measured at a base pressure of ∼1 × 10−8 mbar. Using the background of the Fowler–Nordheim (FN) theory a field enhancement factor (β) of 5.7 × 103 and a threshold field value of 2.5 V μm−1 for 7.5% Ni doped Bi2Se3 were determined by investigating the J–E plot of the FE data. The value of β is three times higher than that of pure Bi2Se3 confirming the superior FE properties. The emission current was found to be very stable with the property of long standing durability as a negligible amount of variation was observed when measured at a constant value of 5 mA for 3 hours. The experimental results signify many opportunities for potential applications of Ni doped Bi2Se3 as a source of electrons in scanning as well as transmission electron microscopy, flat panel displays and as an X-ray generator, etc.

Genetic engineering approach using early Vinca alkaloid biosynthesis genes led to increased tryptamine and terpenoid indole alkaloids biosynthesis in differentiating cultures of catharanthus roseus - Sharma, A.; Verma, P.; Mathur, A.; Mathur, A.K. (Protoplasma, 2018)
Catharanthus roseus today occupies the central position in ongoing metabolic engineering efforts in medicinal plants. The entire multi-step biogenetic pathway of its very expensive anticancerous alkaloids vinblastine and vincristine is fairly very well dissected at biochemical and gene levels except the pathway steps leading to biosynthesis of monomeric alkaloid catharanthine and tabersonine. In order to enhance the plant-based productivity of these pharma molecules for the drug industry, cell and tissue cultures of C. roseus are being increasingly tested to provide their alternate production platforms. However, a rigid developmental regulation and involvement of different cell, tissues, and organelles in the synthesis of these alkaloids have restricted the utility of these cultures. Therefore, the present study was carried out with pushing the terpenoid indole alkaloid pathway metabolic flux towards dimeric alkaloids vinblastine and vincristine production by over-expressing the two upstream pathway genes tryptophan decarboxylase and strictosidine synthase at two different levels of cellular organization viz. callus and leaf tissues. The transformation experiments were carried out using Agrobacterium tumefaciens LBA1119 strain having tryptophan decarboxylase and strictosidine synthase gene cassette. The callus transformation reported a maximum of 0.027% dry wt vindoline and 0.053% dry wt catharanthine production, whereas, the transiently transformed leaves reported a maximum of 0.30% dry wt vindoline, 0.10% catharanthine, and 0.0027% dry wt vinblastine content. © 2017 Springer-Verlag GmbH Austria
Keywords: Agroinfiltration; Strictosidine Synthase (CrSTR); Terpenoid Indole Alkaloids (TIAs)

Unravelling chain confinement and dynamics of weakly entangled polymers in one component nanocomposites - Kruteva, M.; Monkenbusch, M.; Sharma, A.; Allgaier, J.; Hoffmann, I.; Rosi, B.; Dulle, M.; Porcar, L.; Matsarskaia, O.; Richter, D. (Soft Matter, 2025)
Structure and dynamics of polymer chains grafted to a nanoparticle (NP) surface in one component nanocomposites (OCNC) are investigated by small angle scattering (SAXS, SANS) and neutron spin echo (NSE). The OCNC were realized by self-assembly of block-copolymers and subsequent cross-linking of the core. The sizes of the resulting NPs were narrowly distributed. Owing to equal core and shell volumes the melt structure is that of a concentrated colloidal dispersion of cores. The melt structure could be reasonably well described by a Percus-Yevick structure factor. In order to access more deeply the dynamics, three differently labeled materials with labels at the inner- or outer part and the whole graft were studied. The experimental data were evaluated in terms of models allowing for site dependent friction. For this purpose, the Langevin equation containing a friction profile was solved and the dynamic structure factor in terms of its eigenvalues and eigenvectors was compared to the data. The evaluation shows increased friction towards the grafting points. In addition, topological restrictions of motion due to the dense arrangements of micellar cores and the presence of neighboring chains were considered and compared with those of a corresponding melt. Assuming homogenous relaxation of all grafts did not yield a satisfactory data description, but rather at least two differently relaxing chain ensembles had to be considered.